Conserved Regulatory Pathways for Stock-Scion Healing Revealed by Comparative Analysis of Arabidopsis and Tomato Grafting Transcriptomes - Xie, Lulu; Tian, Jianfan; Peng, Lixin; Cui, Qingqing; Liu, Yang; Liu, Jiyang; Li, Fu; Zhang, Siyuan; Gao, Jianchang (Frontiers in Plant Science, 2022)
Many plants can successfully join root and shoot sections at cut surfaces when severed at the stem or hypocotyl. Graft healing is complex and conserved in diverse taxonomic groups with different vascular structures. Herein, we compared transcriptome data from autografted and separated stem sections of Arabidopsis thaliana and tomato (Solanum lycopersicum) to explore changes related to graft healing. Using orthologous gene pairs identified between the two species, temperal expression patterns of evolutionary associated genes in grafted top and bottom, separated top and bottom, and intact stems were exhibited. Genes with expression preference indicate functional diversification of genes related to anatomical structure and cellular development in the two species. Expression profiles of the variable genes revealed common pathways operating during graft healing, including phenylpropanoid metabolism, response to oxygen-containing compounds, xylan and cell wall biogenesis, mitosis and the cell cycle, carboxylic acid catabolism, and meristem structural organisation. In addition, vascular differentiation related NAC domain transcription factors and genome-wide members in Arabidopsis and tomato were used for phylogenetic and expression analysis. Expression differences were largely consistent with sequence differences, reflecting high similarity for protein-coding and regulatory regions of individual clades. NAC proteins mainly clustered in accordance with their reported functions in xylem differentiation or cambium formation. The putative conserved mechanisms suggested by conserved genes and functions could help to expand graft healing theory to a wider range of species, and temporal fluctuations in common pathways imply conserved biological processes during graft healing.